PERLINDUNGAN HUKUM TERHADAP KORBAN SEKSUAL OLEH NEGARA (Studi Kasus di Pengadilan Negeri Mandailing Natal) - Rosmawati Rosmawati (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
When the state is the only party entitled to determine which is called the violation and what is not, then the position of state law and law enforcement officials is higher than the individual and the directly harmed perpetrator inflicted. This type of research in this thesis is a normative  legal research. This study aims to examine  the legal arrangements concering the legal protection by the state  against sexualy victimized. To assess the state legal protection for victims of sexual abuse. To examine the legal protection policy for victims of sexual. Legal arrangement  reganding legal protection bythe state against sexualy victimized. Law No.23 Year 2002 on Child Protection, set up the law for victims of abuse any person knowingly to violence or threats of violence, force, deceit,a series of lies, or persuading a child to commit or tolerate obscene acts, shall be punished with imprisonment minimum of 3 years and maximum fine  of Rp. At Least 300 milillion and Rp.60 milion. Law No 13 of 2006 on the Protection of Witnesses and Victims in preamble this law was born because thet one valid evidence in a court proceeding is whitness and/or victim who hear, see, or experience the occurrence of a crime in an effort to seek and find clarity about criminal offenses commetted by criminals. Legal protection by the state against sexually victimized. The issue of protection against minors who are victims of abuse or sexual assault is not an easy mather for us to practice in reality in everyday life. Particularly in the case of fedofilia or sexual abuse of children under the age where a child should not get the wrong treatment, because every child has a right contained in Law No.23 of 2002 on Child Protection Article 81 paragraph (1) and (2). The rights of children who are victims  of crime are : 1) Getting physical assistance (medical first aid, cloting, shelter and so on). 2) Got a problem resolution support (reporting, legal counsel, and defense). 3) Got back his property. 4) Obtain guidance and rehabilitation. Obtaining compensation (restitution, compensation) of the perpetrator (according to ability) or other parties concered for justice and welfare are concered. Penal sanctions set out clearly the Child Protection Act. Non Penal sanctions against sexual victims, especially children are abstract, meaning is less clear how much compensation